Cardiac arrest due to accidental overdose with norepinephrine dissolved in crystalloid. Issue 12 (9th December 2020) - Hansel, Jan; Ármannsson, Gunnar Skúli
Abstract : Vasoactive agents should be administered through a controlled well-marked infusor pump, ideally via a central venous catheter if given over longer periods of time. During transfer of haemodynamically unstable patients with limited staffing and resources on site, a peripheral vasopressor infusion is sometimes resorted to as a temporary measure of optimising haemodynamic parameters. We report a case of accidental norepinephrine overdose after such practice, resulting in cardiac arrest. It illustrates the importance of careful use and labelling of vasoactive agents during the transport and handover of critically ill patients. Finally, we explore human factor issues associated with transfer from the pre-hospital to the in-hospital environment when such preparations are used.